Using total plasma triacylglycerol to assess hepatic de novo lipogenesis as an alternative to VLDL triacylglycerol - Leanne Hodson; Sion A. Parry; Thomas Cornfield; Catriona Charlton; Wee Suan Low; Charlotte J. Green; Fredrik Rosqvist (Upsala Journal of Medical Sciences, 2020)
Background: Hepatic de novo lipogenesis (DNL) is ideally measured in very low-density lipoprotein (VLDL)-triacylglycerol (TAG). In the fasting state, the majority of plasma TAG typically represents VLDL-TAG; however, the merits of measuring DNL in total plasma TAG have not been assessed. This study aimed to assess the performance of DNL measured in VLDL-TAG (DNLVLDL-TAG) compared to that measured in total plasma TAG (DNLPlasma-TAG). Methods: Using deuterated water, newly synthesised palmitate was determined in fasting plasma VLDL-TAG and total TAG in 63 subjects taking part in multiple studies resulting in n = 123 assessments of DNL (%new palmitate of total palmitate). Subjects were split into tertiles to investigate if DNLPlasma-TAG could correctly classify subjects having ‘high’ (top tertile) and ‘low’ (bottom tertile) DNL. Repeatability was assessed in a subgroup (n = 16) with repeat visits. Results: DNLVLDL-TAG was 6.8% (IQR 3.6–10.7%) and DNLPlasma-TAG was 7.5% (IQR 4.0%−11.0%), and the correlation between the methods was rs = 0.62 (p < 0.0001). Bland–Altman plots demonstrated similar performance (mean difference 0.81%, p = 0.09); however, the agreement interval was wide (−9.6% to 11.2%). Compared to DNLVLDL-TAG, 54% of subjects with low DNL were correctly classified, whilst 66% of subjects with high DNL were correctly classified using DNLPlasma-TAG. Repeatability was acceptable (i.e. not different) at the group level, but the majority of subjects had an intra-individual variability over 25%. Conclusion: DNL in total plasma TAG performed similarly to DNL in VLDL-TAG at the group level, but there was large variability at the individual level. We suggest that plasma TAG could be useful for comparing DNL between groups.